Knowledge, Attitude and Practice in Diabetic Patients in Amreli - Dr Ravikumar R Patel, Dr Milan Chaudhary, Dr Praveen Choudhary (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Diabetes mellitus is a rising public health concern in India, especially in rural and semi-urban regions. Poor knowledge, attitudes, and practices (KAP) among diabetic patients contribute significantly to uncontrolled glycemic levels and related complications. Aims and Objectives: To assess knowledge, attitude and practice among diabetic patients regarding glycemic control and to create awareness to prevent complications and promote healthier outcomes.